Increased Default Mode Network Connectivity in Obsessive–Compulsive Disorder During Reward Processing - Koch, Kathrin; Reeß, Tim J.; Rus, Oana G.; Gürsel, Deniz A.; Wagner, Gerd; Berberich, Götz; Zimmer, Claus (Frontiers in Psychiatry, 2018)
Obsessive-compulsive disorder (OCD) is characterized by anxiety-provoking, involuntary, obsessive thoughts which patients react to with repetitive, compulsive behavior patterns to counteract anxiety. These reactive compulsive behavior patterns are often perceived by the patients as highly remunerating because of their rewarding impact after reducing obsession-related anxiety. Over time these behavior patterns may take on an addictive character and lead to an altered processing of natural rewards in association with an altered functioning of the reward system. Hence, the reward system may become hyposensitive to dopamine as a homeostatic response to continuous activation – a mechanism which has been demonstrated in several neuropsychiatric conditions (Sierra et al., 2015). This continuous activation may go along with a tonic increase of dopamine in the synaptic cleft